Characterization and analysis of the outcome of adults with acute myeloid leukemia treated in a Brazilian University hospital over three decades - Souto Filho,J.T. (2011)
We evaluated the outcome of 227 patients with acute myeloid leukemia during three decades (period 1 - 1980’s, N = 89; period 2 - 1990’s, N = 73; period 3 - 2000’s, N = 65) at a single institution. Major differences between the three groups included a higher median age, rates of multilineage dysplasia and co-morbidities, and a lower rate of clinical manifestations of advanced leukemia in recent years. The proportion of patients who received induction remission chemotherapy was 66, 75, and 85% for periods 1, 2, and 3, respectively (P = 0.04). The median survival was 40, 77, and 112 days, and the 5-year overall survival was 7, 13, and 22%, respectively (P = 0.01). The median disease-free survival was 266, 278, and 386 days (P = 0.049). Survival expectation for patients with acute myeloid leukemia has substantially improved during this 30-year period, due to a combination of lower tumor burden and a more efficient use of chemotherapy and supportive care.